Pengaruh Pemberian Pakan Alami dan Buatan terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Lele Dumbo (Clarias gariepinus Burchell.) di Balai Benih Sentral Noekele Kabupaten Kupang - Rihi, Apriani P (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2019)
Research on the effect of natural and artificial feed on the growth and survival of African catfish at the Noekele Central Seed Center in Kupang Regency, East Nusa Tenggara Province. The center only uses artificial food as fish food while natural food has never been used, therefore researchers are motivated to use natural food then researchers want to see how the influence of natural food is. The purpose of this study is to determine the effect of natural and artificial feeding on the growth and survival of African catfish (Clarias gariepinus Burchell) at the Noekele Central Seed Center in Kupang Regency, knowing the implementation of research results on the learning process of biology at school. The method used in this study is an experimental study using an experimental design that is Completely Randomized Design (CRD) with 3 treatments, each treatment was repeated 3 times namely P0 (Control), P1 (Pellets), and P2 (Silkworms). The data analysis technique used in this study was that this study was analyzed using analysis of variance (Anova) in accordance with the Completely Randomized Design (CRD). The average subsequent treatment was tested using the Duncan Multiple Range Test (DMRT) with a significant level of 5%. The results showed that the treatment of artificial feed (pellets) and natural feed (silk worms) showed significant differences between the treatments for growth and survival of Dumbo catfish (Clarias gariepinus Burchell.). The highest absolute length growth results were found in the P2 treatment of natural silk worm feed of 3.10 cm and the absolute weight of 2.68 grams of survival of African catfish (Clarias gariepinus Burchell.) Highest seeds in natural and artificial food which was 100%.